Značilnosti radialnih malih vodnih turbin s prečnim tokom - Franjić, Krešimir (Strojniški vestnik, 2001)
This paper describes a turbine that is usually known as Banki's turbine. A comparison was made between two specialized types of this turbine: Ossberger's and Cink's turbines. Besides the theoretical basis, which is the same for the two types of turbine, the principal differences are specified. At the end of the paper a conclusion is drawn about the basic control properties and efficiency of both turbines.
Keywords: turbine Banki; turbine radialne; krmiljenje turbin; učinkovitost turbin; turbine; Bankijeva turbina